Some aspects of water and energy budget of a pyroclastic cover. Issue 6 (22nd August 2016) - Reder, Alfredo; Rianna, Guido; Pagano, Luca
Abstract : This paper investigates the soil–atmosphere interaction for a pyroclastic soil. With this aim, a physical model has been developed, consisting of a pyroclastic layer exposed to the atmosphere and extensively monitored to record the various terms of the soil–atmosphere energy balance and layer mass balance. The work interprets a long-term (4-year) monitoring data set in order to estimate the range of variation of the different quantities characterising soil–atmosphere interaction. The physical quantities are obtained from measurements or estimated from mass and energy balance. The study provides estimations on a monthly scale, by averaging over the monitoring period. In addition, mean seasonal values are provided for the energy terms. The paper adopts and compares two different approaches to estimating sensible heat flux and latent heat flux, distinguishing between the different components of short-wave radiation and determining average monthly values for the layer albedo. The main goal of the paper is to provide the range of variation of physical quantities, which are often unusual or in any case are poorly characterised for pyroclastic soils.